Forbush decreases: Algorithm generated dataset - Okike, O. (Data Brief, 2020)
Efforts to correctly detect Forbush decreases (FDs) in the cosmic ray (CR) intensity flux are ongoing (see [2], [7]). The FD data presented here are a part of the data generated in [6] in a recent investigation of the effects of CR anisotropies on the simultaneity of FDs. A part of the simultaneous and non-simultaneous FDs detected from both raw and Fourier transformed CR data are presented. Some of the filtered CR anisotropies are also presented. The datasets are interesting as they provide an opportunity to investigate the interaction of CR anisotropies on FDs. [6] identified FDs from both raw and Fourier transformed CR data. For the FDs identified in the raw data, the impact of diurnal anisopropy was not removed. Additionally, FDs were identified using a careful adjustment for diurnal anisotropy. The results of FD catalogues for ten CR stations are presented. All are calculated with the same method and selection criteria. Thus these catalogues can be united contrary to the indication of [1], allowing comparison of Chree, regression or correction analysis based on CR data from isolated neutron monitors [9]. These data can also be used in the analysis of FD event simultaneity. Several claims on FD event simultaneity by some authors ([5], [8]) using few FDs can be verified using the data. The diagrams show the relationships between raw and Fourier transformed CR data as well as CR anisotropic variations at different locations. The similarities and differences between these figures could be used to discuss the impact of rigidity on diurnal anisotropy and FDs. The quantitative amplitudes of the diurnal anisotropy calculated at the time of FDs could be useful in such investigation. Okike [6] calculated the amplitude of diurnal anisotropies accompanying FDs and are presented here. The large number of strong and small FDs selected from each station for the year 2003 may encourage reanalysis of previous work employing only 3 or 4 FDs in each year. Many studies relating FDs to terrestrial effects have focused on a single FD without strong evidence that it is generalizable to others. This may attract criticism that the conclusions drawn do not extend to all FDs. The diagrams presented here are similar to those presented in [6] for the Climax station. Rather than display separate FD events, the complete intensity variation together with the accompanying FDs are clearly displayed. Solar wind plasma data may be displayed alongside the data for comparative purposes. It is hoped that this approach will answer the numerous objections made to solar-terrestrial analysis involving FDs.